2020
DOI: 10.2116/analsci.19p458
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Grey Nanosystem as Activatable Ratio-colorimetric Probe for Detection of Lead Ions in Preserved Egg

Abstract: A grey system based on the principle of complementary colors was constructed as an activatable probe for sensitive and specific Ratio-colorimetric detection lead ions (Pb 2+) in complex food matrix. This grey system was prepared through mixing purple-red AuNPs-capped glutathione (GSH) and green-blue sulfonated pigment green 7 (SPG7), named SPG7/AuNPs probe. In the presence of Pb 2+ , the strong chelation of Pb 2+ with GSH could trigger the aggregation of AuNPs, leading to the color activation of SPG7. Hence, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Uncontrolled doses of metal ions used Sustainability 2022, 14, 6797 2 of 9 to minimize pickling and maturation times increase the heavy metal residues in pidan, which influences the food's safety and quality. The previous process used lead (Pb 2+ ) as the main addition of divalent metal ions until the lead was reported as hazardous to human health [17,18]. Many results indicated that preserved eggs formed with PbO, CuSO 4 , FeCl 3 , ZnSO 4, and CuSO 4 /ZnSO 4 preparation are potentially dangerous to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled doses of metal ions used Sustainability 2022, 14, 6797 2 of 9 to minimize pickling and maturation times increase the heavy metal residues in pidan, which influences the food's safety and quality. The previous process used lead (Pb 2+ ) as the main addition of divalent metal ions until the lead was reported as hazardous to human health [17,18]. Many results indicated that preserved eggs formed with PbO, CuSO 4 , FeCl 3 , ZnSO 4, and CuSO 4 /ZnSO 4 preparation are potentially dangerous to human health.…”
Section: Introductionmentioning
confidence: 99%